Rural Community Development Through Community Service Program (KKN) in Malaka Hamlet, South Sulawesi Selatan - Nurhikmah, Nurhikmah; Nursalam, Nursalam; Prayetno, Eko; Yumna, Hanim (LPPM STAI Darul Falah, 2024)
The aim of this research is to present the reality of a student's service to society. It also provides religious guidance and assistance as an effort to improve spiritual quality and explore the potential interests and talents of the younger generation in the field of sports through competition. This type of research is qualitative research. Data sources were obtained through observation, interviews and documentation. Data collection techniques included interview, data analysis, and drawing conclusions. The result of this research was the establishment of close ties among the residents regardless of social status and cooperation built in every activity held such as inter-hamlet sports week activities, zakat training, teaching and learning activity and the Malaka Hamlet TPA, Islamic festivals. This activity was held in Malaka Hamlet, Cenrana Baru Village, Cerana District, Maros Regency. The residents of Malaka Hamlet receieved the arrival of Community Service Program (KKN) students. It is also expected that the students would bring the change and contribuition through community empowerment in improving the quality of education, social, and religious.